Ser-tão Cerrado de Guimarães Rosa: espaço movimentante - Gabriel Túlio de Oliveira Barbosa (2013)
The writer João Guimarães Rosa, beyond all the aesthetic elaboration, the mythical and mystical meanings and the deep psychological conception of his characters, also reveals in his work a concern on social and environmental issues involving the regional, national and universal setting of the sertão. In the author's literary project, the sertão (hinterland) and the Brazilian Cerrado transcend their narrative-framing destinations, to conform themselves into coprotagonists of the stories. A space which is at the same time metaphysical and geographical, permeated by a rich and painful history; a very mixed world in the heart of the country. Despite the evidence of a "spatial continuum" in all his narratives, there are socio-spatial nuances interposed among the author's books. We have selected in this research three fictional and allegorical moments of this moving space in Rosas fiction: a) the jagunços system from Grande Sertão: Veredas; b) the gerais in motion from Corpo de Baile; c) and the machinal world from Primeiras Estórias. The fictional nuances are reflexes of the transformations in the space of the sertão, since the decay of the jagunços system in the late nineteenth century and early twentieth century, through the administration of Getúlio Vargas in the 1940s and 1950s, and up to the inauguration of Brasília, in the early 1960s. The author, however, wasnt able to follow up the intense transformations to the Brazilian Cerrado that took place throughout the decades after his death in 1967. The changes in the rationality matrixes undertaken by modernization into Rosas artistic environment induced profound modifications in the dynamics of the natural resources and in the land use system. Thereby, this research aimed, besides the analysis of the works of Guimarães Rosa, to conceive a sensory experience with Rosas sertão at the present time to absorb wisdoms in loco and comprehend the ways in which this moving space articulates itself. The field work experience contributed for the writing of seven episodes/insights, contextualizing the three fictional moments from Grande Sertão: Veredas, Corpo de Baile and Primeiras Estórias and their connections with the present sertão. Its been concluded that despite the external pressure, the city does not end the sertão. The outpouring matter that integrates the sertão/Cerrado will continue to conduct its soul, as long as it continues to be the dimension of human life, of existence, where it is perceived, undergone and affectively experienced by the hinterlanders. It is within this place that should be the resistance core to represent a vehement answer to the attempts of making the space homogenous. We have seen some examples of socio-environmental resistance, whose local proposals come with the inspiration from the literary matrix of Guimarães Rosa, capable of transmitting, illuminating and stimulating an artistic view over the space, like lenses for a captivating perception of the reality.